2009
DOI: 10.1111/j.1528-1167.2009.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in children, adolescents, and young adults with epilepsy

Abstract: Summary Purpose:  The aim of this study was to assess bone mineral density (BMD) in a large population of children, adolescents, and young adults with epilepsy alone or in association with cerebral palsy and/or mental retardation. Methods:  Ninety‐six patients were enrolled in the study. The group comprised 50 males and 46 females, aged between 3 and 25 years (mean age 11 years). The control group consisted of 63 healthy children and adolescents (23 males, 40 females), aged between 3 and 25 years (mean age 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 33 publications
2
56
2
3
Order By: Relevance
“…In a clinical study, treatment with topiramate was not correlated with an increased risk of bone fractures (43). Another clinical study that evaluated BMD in epileptic patients recognized that adjunctive topiramate therapy was significantly correlated with abnormal BMD (6). In the present study, no significant differences in bone strength properties or BMD in the topiramate-treated group were observed.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In a clinical study, treatment with topiramate was not correlated with an increased risk of bone fractures (43). Another clinical study that evaluated BMD in epileptic patients recognized that adjunctive topiramate therapy was significantly correlated with abnormal BMD (6). In the present study, no significant differences in bone strength properties or BMD in the topiramate-treated group were observed.…”
Section: Discussioncontrasting
confidence: 37%
“…Animals were divided into six groups (10 animals/group): [1] control treated with vehicle (0.2% CMC-Na), [2] phenytoin 20 mg/ kg, [3] topiramate 5 mg/kg, [4] topiramate 20 mg/kg, [5] lamotrigine 2 mg/kg, and [6] lamotrigine 10 mg/ kg. Drug doses were selected based on previous reports relevant to phenytoin (24, 25), topiramate (18, 30), and lamotrigine (3,15).…”
Section: Animalsmentioning
confidence: 99%
“…Treatment with lamotrigine is correlated with reduced BMD in children [13]. Furthermore, Coppola et al found that the combination of valproate aid and lamotrigine is related to decreased BMD although these patients had decreased physical activity levels [3].…”
Section: Aeds and Bmdmentioning
confidence: 99%
“…Reduced bone mass density (BMD) has been found in the majority of patients with epilepsy and also 25% of epileptic patients suffered from osteoporosis [3]. Furthermore, BMD of the epileptic children has been found to be significantly lower in comparison to the healthy children; consequently the diagnosis and treatment of this progress is of paramount importance.…”
Section: Introduction Epilepsymentioning
confidence: 99%
“…Of those who had been informed, their epilepsy specialist was the primary source of this information (Epilepsy Action, 2003). Although the results of studies on the impact of AEDs on BMD are diverse, as much as 75 % of epilepsy patients have been found to be osteopenic and up to 25 % osteoporotic (Coppola et al, 2009). The drugs most consistently associated with skeletal abnormalities are those that affect the cytochrome P450 (CYP450) system (e. g. phenytoin, phenobarbital, carbamazepine, valproate) (Vestergaard et al, 2004;Pack et al, 2005;Souverein et al, 2006;Tsiropoulos et al, 2008).…”
Section: Effects On Bone Metabolismmentioning
confidence: 99%